2005
DOI: 10.1142/s0192415x05002606
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn: Potential Roles in Cardiovascular Disease

Abstract: Hawthorn (Crataegus) may play a role in the prevention and treatment of cardiovascular diseases such as hypertension, hyperlipidemia, and in particular, congestive heart failure. Evidence is accumulating that hawthorn may induce anti-ischemia/reperfusion-injury, anti-arrhythmic, hypolipidemic and hypotensive effects. These beneficial effects may in part be due to the presence of antioxidant flavonoid components. While a number of studies have been performed to evaluate the clinical efficacy of hawthorn, an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 30 publications
1
91
0
3
Order By: Relevance
“…Nowadays extracts of Crataegus fruit, leaves and flowers are used for the prevention and treatment of various cardiovascular diseases (hypertension, arrhythmias, congestive heart failure, coronary artery disease, myocardial weakness etc.) due to their positive inotropic and negative chronotropic effects, reduction in coronary spasm, blood pressure and total plasma cholesterol, and for their antioxidant and antiinflammatory properties (Chang et al, 2005;Rigelsky and Sweet, 2002 Nemeikaite-Ceniene et al, 2005, Laughton et al, 1989. Because some of…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays extracts of Crataegus fruit, leaves and flowers are used for the prevention and treatment of various cardiovascular diseases (hypertension, arrhythmias, congestive heart failure, coronary artery disease, myocardial weakness etc.) due to their positive inotropic and negative chronotropic effects, reduction in coronary spasm, blood pressure and total plasma cholesterol, and for their antioxidant and antiinflammatory properties (Chang et al, 2005;Rigelsky and Sweet, 2002 Nemeikaite-Ceniene et al, 2005, Laughton et al, 1989. Because some of…”
Section: Discussionmentioning
confidence: 99%
“…As we know, oxidation of the low-density lipoprotein (LDL) cholesterol plays an important role in atherosclerosis [73]. This accumulation causes a cascade of inflammatory processes, resulting in an unstable atherosclerotic plaque that ultimately bursts, causing myocardial infarction [74].…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…The use of hawthorn for the treatment of cardiovascular heart disease dates back to the late 1800s [6, 7]. Current claims suggested that hawthorn could be used as an alternative therapy for various cardiovascular diseases, such as angina, hypertension, hyperlipidemia, arrhythmia, and New York Heart Association (NYHA) functional class II congestive heart failure [8, 9]. Nowadays, it is gaining attention for its potential cardiovascular enhancing and protective properties [10] and numerous laboratory tests and clinical trials have demonstrated hawthorn's efficacy in the treatment or prevention of cardiovascular diseases and the most substantial evidence for clinical benefits of hawthorn is its use in chronic congestive heart failure (CHF) [11].…”
Section: Introductionmentioning
confidence: 99%
“…1,2) These extracts exert several pharmacological and clinical effects, such as antiischemia/reperfusion-injury, anti-arrhythmic, hypolipidemic, and hypotensive effects. 1,2) Flavonoids and procyanidins are considered to be the two main active constituents. 2) Species of Chinese hawthorn, particularly Crataegus pinnatifida and Crataegus pinnatifida Bge.…”
mentioning
confidence: 99%